Restoring ankle dorsiflexion range of motion in athletes: an individualized clinical decision-making system - Tourillon, Romain; M'Baye, Massamba; Smith, Michelle (Frontiers in Sports and Active Living, 2025)
BackgroundAnkle dorsiflexion range of motion plays a pivotal biomechanical role within the lower limb with implications both in rehabilitation, injury risk reduction and athletic performance. However, clinicians often lack practical guidance on diagnosing and differentiating the various joints or structures that have been shown to have a role in ankle dorsiflexion range of motion restriction.Clinical questionTo move beyond the “one size fits all approach” paradigm in musculoskeletal rehabilitation, we propose addressing the 2 following questions: (1) How can clinician utilize the weight-bearing lunge test findings to develop a clinical-decision making system for ankle dorsiflexion range of motion assessment? and (2) How can this system guide individualized interventions to restore ankle dorsiflexion range of motion specific to each athlete's needs?.SolutionsWe outline a 3-step framework for improving ankle dorsiflexion range of motion restriction: (1) having a quantitative and qualitative assessment using the weight-bearing lunge test to identify joint or structure involvement, (2) having confirmatory diagnostic testing to pinpoint mobility restrictions of the joint or structures involved, and (3) proposing targeted interventions based on individual findings, ensuring a personalized rehabilitation approach rather than a generalized global protocol.Clinical applicationThis rehabilitation practice commentary addresses a notable gap in the existing literature on clinical choices regarding ankle dorsiflexion restriction treatment. By integrating this individual clinical decision-making system, clinicians can enhance rehabilitation and performance optimization beyond standard treatment methods.